1998
DOI: 10.2307/2446530
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of shoots and tumors of in vitro habituated rhododendron ‘montego’ (Ericaceae) cultures with tissue proliferation

Abstract: Tissue proliferation (TP) is characterized primarily by the formation of galls or tumors at the crown of container-grown rhododendrons that were initially propagated in vitro. In the cultivar 'Montego', TP-like symptoms are first observed in vitro as shoot clusters with small leaves and nodal tumors. In addition, unlike the normal in vitro non-TP (TP-) shoots, in vitro TP (TP+) shoots proliferate rapidly without the presence of the plant growth regulator cytokinin in the tissue culture medium. Comparisons of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…During the past decade, numerous anatomical and ultrastructural studies of diverse species cultivated in vitro have been reported (Johansson et al, 1992;Sallanon et al, 1993;Gribble et al, 1996;Noe  and Bonini, 1996;Mercure et al, 1998;Olmos and Hellõ Ân, 1998). However, there is sparse information on jojoba anatomy in either ex vitro or in vitro conditions (Birnbaum et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, numerous anatomical and ultrastructural studies of diverse species cultivated in vitro have been reported (Johansson et al, 1992;Sallanon et al, 1993;Gribble et al, 1996;Noe  and Bonini, 1996;Mercure et al, 1998;Olmos and Hellõ Ân, 1998). However, there is sparse information on jojoba anatomy in either ex vitro or in vitro conditions (Birnbaum et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…1). Most of the shoots were highly branched, had short internodes, small leaves (2-3 mm long) and nodal tumors (Mercure et al, 1998). These shoots are referred to as TP(+) dwarf shoots.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology of TP also appears to be similar to that of lignotubers, which are woody outgrowths at the stem base that contain numerous dormant buds (Del Tredici, 1992). However, TP tumors do not generally exhibit normal lignotuber characteristics (Brand and Kiyomoto, 1994;Del Tredici, 1992;Mercure et al, 1998). The most widely accepted theory is that TP results from epigenetic changes that are induced by the tissue culture process (Brand and Kiyomoto, 1997;Linderman, 1993).…”
mentioning
confidence: 99%